ANALISIS PROGRAM MARKET DAY DALAM MENGUKUR KEMAMPUAN KEWIRAUSAHAAN SISWA SEKOLAH DASAR - Aliffadila, Siti Zahra Viesya; Nugraha, Widdy Sukma; Rohani; Pujiasti, Dea Asri; Denni, Irdam (caXra: Jurnal Pendidikan Sekolah Dasar, 2024)
Market Day is one of the development activities and results of innovation from several learning models or methods where students will simulate selling to improve elementary school students' entrepreneurial abilities. The aim of Market Day is for students to be able to learn through their direct experience during the learning process, thereby providing deep meaning and impressions for students. Researchers use qualitative descriptive methods to describe research results in narrative form about each research object individually. The results of this research show that the Market Day program in its implementation has a foundation, planning and suitability and the entrepreneurial abilities of SDN 2 Pakuwon students are adequate so that this program can become one of the programs that can improve entrepreneurial abilities in elementary school students.